Investigating the use and acceptance of technologies by professors in a higher education institution - Costa, Carolina (2019)
This article analyses the use and acceptance of technologies by professors in the teaching and learning context in a higher education institution. In the empirical study, a questionnaire based on the technology acceptance model was applied. The results indicated that the most used technologies are Moodle, Facebook and YouTube and it was concluded that in general, those technologies are well accepted. Few statistically significant differences between respondents’ gender, scientific areas or ages were found, revealing that the use of those technologies is already widespread in the studied institution. Results also showed that perceived usefulness and perceived ease of use are two important determinants of Moodle acceptance, and that the majority of respondents did not know the MOOC concept. This article is valuable for researchers in the area and for professors that want to implement the use technologies in the teaching and learning context.